Hubungan Adiksi Internet dengan Depresi dan Kecemasan pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa Angkatan 2018 dan 2019 - Kadek Ayu Trishanti Devi; Komang Trisna Sumadewi; I Wayan Eka Arsana (Aesculapius Medical Journal, 2022)
Excessive use of internet can cause internet addiction condition especially in students. Internet addiction has negative impact on the onset of psychiatric symptoms such as depression and anxiety. The aims of this research was to determine the relationship between internet addiction with depression and anxiety in medical students of the Faculty of Medicine and Health Sciences, Warmadewa University class of 2018 and 2019. The type of this research was an analytic correlation study with a cross-sectional design which conducted from November – December 2021 used simple random sampling for the sampling technique then obtained 80 samples. Data of internet addiction level, depression level and anxiety level collected by questionnaire. Data univariate analysis used frequency distribution and bivariate analysis used Spearman rank correlation test. The final result of bivariate analysis showed p value <0,05 which means there is a significant positive correlation between internet addiction with depression (p=0,003) and between internet addiction with anxiety (p=0,003). It also showed the correlation between internet addiction with anxiety (r=0,332) greater than the correlation between internet addiction with depression (r=0,323).